2017
DOI: 10.1016/j.pmpp.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and secretome of two Pythium species during infection and saprophytic growth

Abstract: TRANSCRIPTOME AND SECRETOME OF TWO PYTHIUM SPECIES DURING INFECTION AND SAPROPHYTIC GROWTHIn the first part of this dissertation, I describe how we obtained and analyzed the full complement of transcripts -the transcriptome-and the set of secreted proteins -the secretomeof Pythium irregulare and Pythium iwayamai isolates when they were infecting plant hosts and when they were growing saprophytically. Additionally, these two treatments were performed at two different temperatures (4˚ and 19˚C). The assembled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…The presence of genes encoding proteases families such as subtilisin-related proteases, metalloproteases, and E3 ligases, inducing necrosis and cell-wall degradation in the core Pythium spp. genes and the absence or lack of RXLR effectors in Pythium support its non-host specificity and necrotrophic lifestyle [ 117 , 118 , 119 ]. Unlike Phytophthora , Pythium spp.…”
Section: Virulence Mechanism Of Pythium Spp and Challenges In Resistant Breeding Against Pythium Spmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of genes encoding proteases families such as subtilisin-related proteases, metalloproteases, and E3 ligases, inducing necrosis and cell-wall degradation in the core Pythium spp. genes and the absence or lack of RXLR effectors in Pythium support its non-host specificity and necrotrophic lifestyle [ 117 , 118 , 119 ]. Unlike Phytophthora , Pythium spp.…”
Section: Virulence Mechanism Of Pythium Spp and Challenges In Resistant Breeding Against Pythium Spmentioning
confidence: 99%
“…Unlike Phytophthora , Pythium spp. have been observed to lack RXLR effectors with avirulence activities [ 118 , 119 ]. The absence of these avirulence factors has been correlated with the lack of gene-for-gene resistance against Pythium spp.…”
Section: Virulence Mechanism Of Pythium Spp and Challenges In Resistant Breeding Against Pythium Spmentioning
confidence: 99%
“…Resistance to necrotrophic pathogens is generally quantitative (Bruehl 1983;Raajimakers et al 2009). The Pythium genome lacks RxLR effectors, which are known in other oomycete species to be responsible for gene-for-gene resistance interactions with the host plant (Lévesque et al 2010;Caballero and Tisserat 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Elicitins may be important for infection, as they trigger necrosis in host cells (Ponchet et al, 1999). Although elicitins were found to be abundant in P. irregulare and P. iwayamai, the similarity between their elicitins was never more than 70% (Caballero & Tisserat, 2016). Lévesque et al (2010) reported that P. ultimum encodes more E3 ligases than other oomycetes, which are known to degrade host response proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation